CAVITATION EROSION WEAR OF METALLIC SPECIMENS USING THE NEW COMPACT ROTATING DISK DEVICE - Bazanini, G.; Bressan, J. D.; Klemz, M. A. (Revista de Engenharia Térmica, 2008)
A more compact version of the rotating disk device (where a disk with cavitation inducers and specimens fixed on it rotates in water to provide cavitating flow) is used here to study the failure by cavitation in metallic specimens. The damage in the specimens is measured by mass loss versus exposition time to cavitating flow diagrams. Images of the test specimens obtained by electronic microscope are also shown and discussed. After 25 hours working in cavitating conditions, aluminum, brass and cast iron are weared by the cavitation phenomenon, resulting in pitting formation and mass loss. After each 5 hours operating in cavitating conditions, the specimens are cleaned by ultrasound, dried and weighted in a digital balance to obtain the mass loss in the process by comparing to its initial weight. All specimens, aluminum, brass and cast iron, were eroded by cavitation although in the aluminum the mass loss was lesser than the expected. The brass specimen was eroded as expected, mas no mass loss could be attained for the cast iron due to specimen oxidation.